Morphological and thermal stability analysis of Sn/C electrodes synthesized through impregnation and precipitation methods for CO2 electroreduction - Eviani, Mitra; Prakoso, Tirto; Kusdiana, Dadan; Widiatmoko, Pramujo; Devianto, Hary (International Journal of Renewable Energy Development, 2025)
This study investigates tin (Sn) based electrodes supported by graphite for the electrochemical reduction of carbon dioxide (ECO2R) to formic acid, comparing precipitation and impregnation synthesis methods. Electrodes were characterized using Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Thermogravimetric Analysis (TGA), Cyclic Voltammetry (CV), Chronoamperometry, and Electrochemical Impedance Spectroscopy (EIS). The precipitation method yielded higher Sn content (91.22%) and superior thermal stability (3% mass loss at 1000°C vs. 45% for impregnation). Morphological analysis through SEM revealed precipitation-synthesized electrodes exhibited more uniform Sn particle distribution across the graphite surface, while impregnation resulted in larger Sn agglomerates with less homogeneous coverage, significantly influencing electroactive surface area and catalytic performance. The electrochemical performance of electrodes was tested using H-cell. CV showed decreased cathodic current for Sn/C electrodes compared to pure graphite in CO2-saturated electrolyte, while chronoamperometry indicated slightly better sustained performance for precipitation-synthesized electrodes with stabilized current densities after 3 hours of operation. EIS analysis suggested the precipitation method yields a marginally lower ohmic resistance (28.8 Ω vs. 29.8 Ω), resulting in a more favorable electrode structure for overall catalytic activity. Both methods showed lower ohmic resistance than that of pure graphite (38.1 Ω), the precipitation-synthesized Sn/C electrode emerged as the preferred selection for ECO2R to formic acid, balancing high Sn content, thermal stability, superior durability, and better Faradaic efficiency. The observed performance differences were attributed to distinct metal-support interactions formed during synthesis, with precipitation creating stronger metal-carbon bonds that enhance stability but potentially limit certain active sites necessary for optimal CO2 reduction kinetics. This comprehensive characterization revealed that the precipitation-synthesized electrode offers the most promising foundation for further development, potentially through process optimization, hybrid synthesis approaches, or targeted doping strategies to enhance catalytic activity while maintaining the advantageous stability characteristics.